ACCURACY WEANING FOOD FEEDING TO BABY AGE 6-12 MONTHS AT SINGKALAN VILLAGE BALONGBENDO DISTRICT SIDOARJO REGENCY - heni purwati; ETIK KHUSNIYATI (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Weaning Food feeding is a food given to babies in order to support the growth of babies aged 6-12 months. Weaning Food is given during the transition period from 6 months to 12 months, which is a child-prone period. Because if weaning food feeding in this transitional period is less precise, will be the beginning of malnutrition in children, which can affect the growth and development of health in the future (Sitompul, 2012). During this time many mothers who pay less attention to weaning food feeding in her child. Some were given before 6 months this affects the development of children. Babies were ready to eat solid foods, either growing or psychologically, at 6-9 months of age. The ability of newborns to digest, absorb, and metabolize foodstuffs was adequate, but limited to only a few functions. There were several signs that indicate that the baby was ready to receive weaning food (madya, 2012). To prevent the occurrence of malnutrition, then gsiycf issued the requirement of weaning food, which is punctual, weaning food given from the age of 6 months, nutritious, weaning food must contain enough energy, protein, vitamins and minerals to support growth optimal, safe: preparation and when given, weaning food should be clean, appropriate ways of giving: give weaning food in line with hunger and appetite indicated by the baby. Type of weaning food, number, frequency and mode of administration adjusted for baby age (dias, 2013). Based on toddler weighing at posyandu, found 26,518 balita malnutrition nationally. Cases of malnutrition in question was determined based on the calculation of body weight according to Zscore <-3 standard deviation of children standard (very skinny toddler). Meanwhile, according to Riskesdas 2013, the prevalence of very underweight nutrition in babies by 5.3%. If estimated against the number of under-five target (S) registered in the posyandu reporting (21,436,940), the estimated number of malnourished children under five (1.1 million people) (Ministry of Health RI, 2015). The prevalence of malnutrition was one of the indicators of mdgs and strategic plan (renstra) of east java provincial health office, measured by weight loss by age (bb / u), ie from very low body weight and weight loss. Based on the results of psg 2014, east java had reached the number below the mdgs (15.0%) and renstra (15.0%) of 12.3% (less weight 10.3% and very low weight 2.0%) (dho, east java, 2015). Based on preliminary studies conducted by researchers, the problem of improper weaning food giving also occurred in singkalan village, balongbendo sub-district, sidoarjo regency. Based on primary data obtained from public health service kecamatan, there are Â± 52% of babies less than two months have been given food other than breast milk.